The Influence of Parenting Styles and Socioeconomic Status on Learning Motivation and Student Learning Outcomes in Junior High School: A Systematic Literature Review - Istail Istail; Adi Asmara (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to systematically examine the influence of parenting styles and family socioeconomic status on learning motivation and student learning outcomes at the junior high school level. The method used is a systematic literature review by examining various relevant empirical research findings from 2020 to 2025. The results show that parenting styles, particularly authoritative parenting, are positively associated with increased learning motivation, academic independence, and student learning achievement. Authoritative parenting, characterized by warmth, open communication, and guided autonomy, proves most effective in building students' intrinsic motivation. Conversely, authoritarian, permissive, and neglectful parenting styles tend to hinder students' academic development. Family socioeconomic status also plays an important role through the provision of learning facilities, parental educational support, home environment quality, and access to adequate learning resources. Learning motivation serves as a mediating variable that bridges the influence of parenting styles and socioeconomic status on student learning outcomes. In addition to family factors, pedagogical leadership of teachers and schools contributes to creating a conducive learning environment. This study recommends strengthening democratic parenting, improving educational access for low socioeconomic status families, and developing pedagogical leadership in schools to optimize student learning outcomes.